Revision of the genus Campylaimus (Diplopeltidae, Nematoda) with description of four new species from the Sea of Japan - Fadeeva, Natalia; Mordukhovich, Vladimir; Zograf, Julia (Zootaxa, 2016)
Four new Campylaimus species are described from the deep-sea sediments of the Sea of Japan at depths of about 500‒3400 m. Campylaimus orientalis sp. nov. is characterized by having a body of moderate length, clearly annulated cuticle, a small rhomboid mouth opening which is displaced on the dorsal side of body, a gap between the unequal limbs of the amphid, prominent narrow longitudinal alae and cephalated spicules. Campylaimus minutus sp. nov. is characterized by having a cylindrical body, very weak annulations, amphids with a short dorsal limb (25–44% of pharynx length) and a ventral limb completely fused with lateral alae of equal width; and lateral alae extending from the base of the amphid to the tail tip. Campylaimus amphidialis sp. nov. is characterized by having the combination of a very long amphidial fovea occupying nearly the entire length of the pharynx; and a well defined boundary between the ventral amphid limb and lateral alae. The distinctive feature of Campylaimus pulcher sp. nov. is the elongated loop-shaped amphid with nearly equal parallel limbs and prominent narrow longitudinal alae; and cephalated spicules without a gubernaculum. The diagnosis of the genus Campylaimus is emended and an identification key to species, based mainly on form and length of amphidial fovea, width of lateral alae, and copulatory apparatus is given. The genus Campylaimus now includes nineteen valid species. Two species are considered as species inquirendae, mainly because of incomplete descriptions.